Molecular identification of pseudomonas sp. from tap water and filtered water / Rasyidah Wafa Jainudeen - Jainudeen, Rasyidah Wafa (2018)
Pseudomonas sp. is a Gram negative opportunistic bacteria that usually found in watery environment such as tap water, filtered water and any surfaces that have contact with water. Besides, this infective bacteria can be found in soil, canned food, and also cosmetic which can cause harm to low immune system person. In this research, tap water and filtered water were collected in order to identify the bacteria through molecular identification by using specific PCR primers, Pse435F and Pse686R. Total of six water samples, were collected from UiTM Kuala Pilah and public area around Kuala Pilah and were isolated for each samples on Pseudomonas Isolation Agar (PSI) at 35°C for 48 hours. The successfully isolated bacteria, Pseudomonas sp. were stained by Gram staining and further undergo molecular identification. The pink stained Pseudomonas sp. were successfully amplified approximately 251 bp in all samples.